Analysis of Viral Membranes Formed in Cells Infected by a Vaccinia Virus L2-Deletion Mutant Suggests Their Origin from the Endoplasmic Reticulum - Maruri-Avidal, Liliana (American Society for Microbiology, 2013)
Assembly of the poxvirus immature virion (IV) membrane is a poorly understood event that occurs within the cytoplasm. At least eight viral proteins participate in formation of the viral membrane. Of these, A14, A17, and D13 are structural components whereas A6, A11, F10, H7, and L2 participate in membrane biogenesis. L2, the object of this study, is conserved in all chordopoxviruses, expressed early in infection, and associated with the endoplasmic reticulum (ER) throughout the cell and at the edges of crescent-shaped IV precursors. Previous studies with an inducible L2 mutant revealed abortive formation of the crescent membrane. However, possible low-level L2 synthesis under nonpermissive conditions led to ambiguity in interpretation. Here, we constructed a cell line that expresses L2, which allowed the creation of an L2-deletion mutant. In noncomplementing cells, replication was aborted prior to formation of mature virions and two types of aberrant structures were recognized. One consisted of short crescents, at the surface of dense masses of viroplasm, which were labeled with antibodies to the A11, A14, A17, and D13 proteins. The other structure consisted of “empty” IV-like membranes, also labeled with antibodies to the viral proteins, which appeared to be derived from adjacent calnexin-containing ER. A subset of 25 proteins examined, exemplified by components of the entry-fusion complex, were greatly diminished in amount. The primary role of L2 may be to recruit ER and modulate its transformation to viral membranes in juxtaposition with the viroplasm, simultaneously preventing the degradation of viral proteins dependent on viral membranes for stability.